A Multipurpose First‐in‐Human Study With the Novel CXCR7 Antagonist ACT‐1004‐1239 Using CXCL12 Plasma Concentrations as Target Engagement Biomarker. Issue 6 (15th February 2021) - Huynh, Christine; Henrich, Andrea; Strasser, Daniel S.; Boof, Marie‐Laure; Al‐Ibrahim, Mohamed; Meyer Zu Schwabedissen, Henriette E.; Dingemanse, Jasper; Ufer, Mike
Abstract : The C‐X‐C chemokine receptor 7 (CXCR7) has evolved as a promising, druggable target mainly in the immunology and oncology fields modulating plasma concentrations of its ligands CXCL11 and CXCL12 through receptor‐mediated internalization. This "scavenging" activity creates concentration gradients of these ligands between blood vessels and tissues that drive directional cell migration. This randomized, double‐blind, placebo‐controlled first‐in‐human study assessed the safety, tolerability, pharmacokinetics, and pharmacodynamics of ACT‐1004‐1239, a first‐in‐class drug candidate small‐molecule CXCR7 antagonist. Food effect and absolute bioavailability assessments were also integrated in this multipurpose study. Healthy male subjects received single ascending oral doses of ACT‐1004‐1239 ( n  = 36) or placebo ( n  = 12). At each of six dose levels (1–200 mg), repeated blood sampling was done over 144 hours for pharmacokinetic/pharmacodynamic assessments using CXCL11 and CXCL12 as biomarkers of target engagement. ACT‐1004‐1239 was safe and well tolerated up to the highest tested dose of 200 mg. CXCL12 plasma concentrations dose‐dependently increased and more than doubled compared with baseline, indicating target engagement, whereas CXCL11 concentrations remained unchanged. An indirect‐response pharmacokinetic/pharmacodynamic model well described the relationship between ACT‐1004‐1239 and CXCL12 concentrations across the full dose range, supporting once‐daily dosing for future clinical studies. At doses ≥ 10 mg, time to reach maximum plasma concentration ranged from 1.3 to 3.0 hours and terminal elimination half‐life from 17.8 to 23.6 hours. The exposure increase across the dose range was essentially dose‐proportional and no relevant food effect on pharmacokinetics was determined. The absolute bioavailability was 53.0% based on radioactivity data after oral vs. intravenous 14 C‐radiolabeled microtracer administration of ACT‐1004‐1239. Overall, these comprehensive data support further clinical development of ACT‐1004‐1239.